MITIGASI RISIKO PERPAJAKAN MELALUI PENGAMPUNAN PAJAK PADA WAJIB PAJAK ORANG PRIBADI - Bayu Sarjono (Politeknik Ubaya, 2018)
Tax is one of the major source of Indonesia state revenue to develop the country but the realization of tax revenues has not reached the target. One of the efforts made by the government in increasing tax revenues through tax amnesty programs. For example, Taxpayer A (individual tax payer) follows tax amnesty because there are still unreported assets that are found inside and outside the country by redemption payment. The benefits of following tax annesty programs are to mitigate tax risk by obtaining a remission of taxes, could eliminate tax penalties, and not being subject to criminal sanctions in the taxation. Taxpayers A (individual tax payer) has the obligation to declare of their offshore assets periodically for three years since the Statement Letter on tax amnesty issued.